The effect of expertise on employee performance with work motivation as intervening variable - Syawaluddin, Syawaluddin; Erwin, Erwin; Joni, Joni (Management and Entrepreneurship: Trends of Development, 2020)
This study is aimed at analyzing the effect of expertise on employee performance in PT Dinamika Abadi Medan with work motivation as an intervening variable. This research involved 124 company employees. Data analysis tools used in hypothesis testing were validity, reliability and path analysis. The research results showed that expertise had a significant effect on employee performance in PT Dinamika Abadi Medan. It means that the higher the expertise provided, the higher the employee performance in PT Dinamika Abadi Medan. Expertise significantly impacted the work motivation of employees in PT Dinamika Abadi Medan. It means that the higher the expertise provided, the higher the work motivation of employees in PT Dinamika Abadi Medan. Work motivation had a significant effect on employee performance in PT Dinamika Abadi Medan. This case means that the higher the employee work motivation, the higher the employee performance in PT Dinamika Abadi Medan. The empirical test resulted in Z count (36.0) > Z table (1.96) so that work motivation could mediate the relationship between expertise and employee performance. Therefore, H4 was accepted. This case means that the higher the expertise provided, the higher the employee work motivation so that employee performance increased as well.JEL Classification: O15, M51, M54.